The Endothelial Glycocalyx: Physiology and Pathology in Neonates, Infants and Children - Puchwein-Schwepcke, Alexandra; Genzel-Boroviczény, Orsolya; Nussbaum, Claudia (Frontiers in Cell and Developmental Biology, 2021)
The endothelial glycocalyx (EG) as part of the endothelial surface layer (ESL) is an important regulator of vascular function and homeostasis, including permeability, vascular tone, leukocyte recruitment and coagulation. Located at the interface between the endothelium and the blood stream, this highly fragile structure is prone to many disruptive factors such as inflammation and oxidative stress. Shedding of the EG has been described in various acute and chronic diseases characterized by endothelial dysfunction and angiopathy, such as sepsis, trauma, diabetes and cardiovascular disease. Circulating EG components including syndecan-1, hyaluronan and heparan sulfate are being evaluated in animal and clinical studies as diagnostic and prognostic markers in several pathologies, and advances in microscopic techniques have enabled in vivo assessment of the EG. While research regarding the EG in adult physiology and pathology has greatly advanced throughout the last decades, our knowledge of the development of the glycocalyx and its involvement in pathological conditions in the pediatric population is limited. Current evidence suggests that the EG is present early during fetal development and plays a critical role in vessel formation and maturation. Like in adults, EG shedding has been demonstrated in acute inflammatory conditions in infants and children and chronic diseases with childhood-onset. However, the underlying mechanisms and their contribution to disease manifestation and progression still need to be established. In the future, the glycocalyx might serve as a marker to identify pediatric patients at risk for vascular sequelae and as a potential target for early interventions.